Creativity and Entrepreneurial Intentions in Peruvian University Students - Castillo-Chinchay, Eliana Lizet; Ríos-Lama, Cristian Armando; Vargas-Merino, Jorge Alberto (LACCEI, 2024)
Currently, individuals’ entrepreneurial intentions are closely linked to creative talent, particularly among students. Based on this premise, the present research aims to determine the existence of a relationship between creativity and entrepreneurial intention in students from universities in Lima Norte, Peru, in 2023. A basic methodology was employed, utilizing a quantitative approach, non-experimental design, and correlational level with a sample of 107 university students. According to the results, a high level of creativity was found in 59% of the students, along with a high level of entrepreneurial intention in 61%. Furthermore, a relationship was demonstrated between the creativity variable and the attitude (0.749), behavioral control (0.681), and subjective norm (0.608) dimensions. In conclusion, there is a direct and positive relationship between the creativity variable and entrepreneurial intention, with a correlation value of 0.741 in university students from Lima Norte, Peru, in 2023